THE EFFECT OF USING SMALL GROUP DISCUSSION IN SPEAKING ABILITY AT TENTH GRADERS OF SMAN 1 JALANCAGAK (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
This study aims to determine the effectiveness of discussion techniques on the speaking ability of 10th graders of SMAN 1 Jalancagak in the 2021/2022 academic year. The method used is the Small Group Discussion method. This study uses a quasi-experimental method (quantitative method), where there are manipulated activities, one class uses the small group discussion method and the other class uses the discussion method only. The object of this research is the students of SMAN 1 Jalancagak for the academic year 2021/2022. Then, choose two classes at random as a sample. The number of students is 74 students, each class consists of 37 students. Of the two classes, class X Mipa 1 as the experimental class received the treatment of the small group discussion method and class X Mipa 3 as the control class that received the treatment of the discussion method. Based on the results of research conducted by previous researchers, it can be said that the use of the small group discussion method has a positive effect on students' speaking ability. Therefore, is the small group discussion method still effective during the current pandemic?
Keywords: Speaking Ability; Small Group Discussion Method